Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

-10n + 3(8+8n)=-6(n-4)

Sagot :

First we have to multiply factor by every argument from the parenthesis.
-10n+3(8+8n)=-6(n-4)
-10n+3*8+3*8n=-6n+6*4
-10n+24+24n=-6n+24
24+14n=-6n+24        /-24
14n=-6n               /+6n
20n=0                 /:20
n=0 - its the answer